2012
DOI: 10.1037/a0024611
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions for moral judgments depends on the type of emotion and moral scenario.

Abstract: Emotions seem to play a critical role in moral judgment. However, the way in which emotions exert their influence on moral judgments is still poorly understood. This study proposes a novel theoretical approach suggesting that emotions influence moral judgments based on their motivational dimension. We tested the effects of two types of induced emotions with equal valence but with different motivational implications (anger and disgust), and four types of moral scenarios (disgust-related, impersonal, personal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 45 publications
7
134
2
7
Order By: Relevance
“…As such, the current results are also consistent with the proposed role of emotion in deontological judgments (Schnall et al, 2008;Van Dillen et al, 2012;Wheatley and Haidt, 2005). More specifically, the successful induction of avoidance-related emotions (e.g., disgust or fear) may lead to deontological moral judgments (Harle and Sanfey, 2010;Ugazio et al, 2012). Furthermore, according to the somatic-marker theory of addiction, the medial prefrontal cortex is the key brain region for generating and integrating emotional signals (somatic-markers), which arise in anticipation of the affective and social consequences of different courses of action (e.g., utilitarian vs. deontological), crucially guiding decision-making (Verdejo-Garcıa and Bechara, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As such, the current results are also consistent with the proposed role of emotion in deontological judgments (Schnall et al, 2008;Van Dillen et al, 2012;Wheatley and Haidt, 2005). More specifically, the successful induction of avoidance-related emotions (e.g., disgust or fear) may lead to deontological moral judgments (Harle and Sanfey, 2010;Ugazio et al, 2012). Furthermore, according to the somatic-marker theory of addiction, the medial prefrontal cortex is the key brain region for generating and integrating emotional signals (somatic-markers), which arise in anticipation of the affective and social consequences of different courses of action (e.g., utilitarian vs. deontological), crucially guiding decision-making (Verdejo-Garcıa and Bechara, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Although future work is required to explore these effects, we suggest that the perception of fear in specific individuals may lead to an aversion to harming those individuals even when doing so may lead to saving other people, as in high-conflict scenarios (Crockett et al, 2010). On the other hand, low-conflict scenarios (e.g., causing harm for selfish benefit) may trigger moral disgust (Ugazio et al, 2012;Wheatley and Haidt, 2005).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study comparing disgust with anger (Ugazio et al, 2012) indicated that people's choices when judging a moral story depended on the type of emotions elicited, whilst the influence the emotions exert on their judgments depended on the motivational aspect (i.e., approach and withdrawal). More precisely, when people are angry, they tended to judge moral situations in a more tolerant manner; whereas when they were under the influence of disgust, they judged the situation in the opposite manner (i.e., less tolerant).…”
Section: Claim 3: Disgust Is Just Anger In Disguisementioning
confidence: 99%
“…It is necessary to train students how to value the material, to identify what is important and not to learn everything. Researches also show that emotions and moral judgment about the material significantly influence students' motivation (Ugazio, Lamm, & Singer, 2012). While testing the preconceptions of students about whether their actions will have a negative or neutral outcome, the results show that preconceptions affect motivation but are unreliable (Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010).…”
Section: Introductionmentioning
confidence: 99%